The Utilization of Keprok Orange Fruit (Citrus reticulata) Juice in Mozarella Cheese Manufacturing (Jurnal Ilmu dan Teknologi Hasil Ternak, 2012)
The aim of this study was to know the effect of Keprok Orange Fruit (Citrus reticulata) Juice as a direct acidification to yield, meltability, stretchability, protein and moisture content to Mozarella cheese. The result showed that Keprok orange fruit juice gave a highly significant effect (P<0.01) on protein content of Mozzarella cheese. In the otherwise gave a significant effect (P<0.05) on yield, meltability and moisture content of Mozzarella cheese but did not give a significant effect (P>0.05) on stretchability. The conclusion of this research was the Keprok orange fruit juice concentration of 3 % was the best concentration and suggested to use on Mozzarella cheese manufacturing. Key words: Keprok orange fruit (Citrus reticulata), Mozarella cheese manufacturing